Oceanology the true account of the voyage of the Nautilus by Zoticus de Lesseps, 1863 - Hawkins, Emily (Ology books, 2009)
Purports to be the journal of Zoticus de Lesseps, written on an ill-fated 1863 voyage accompanying Captain Nemo to explore the mysteries of the deep sea.